Sex-specific association of hyperuricemia with cardiometabolic abnormalities in a military cohort: The CHIEF study. Issue 12 (March 2020) - Lin, Yu-Kai; Lin, Yen-Po; Lee, Jiunn-Tay; Lin, Chin-Sheng; Wu, Tsung-Jui; Tsai, Kun-Zhe; Su, Fang-Ying; Kwon, Younghoon; Hoshide, Satoshi; Lin, Gen-Min
Abstract : Abstract: Hyperuricemia has been associated with metabolic syndrome, and the association with various cardiometabolic risk factors may be affected by sex. We made a cross-sectional examination in a military cohort of 6738 men and 766 women, aged 18 to 50 years of Taiwan in 2013 to 2014. Hyperuricemia were defined as serum uric acid levels ≥7.0 mg/dL for men and ≥5.7 mg/dL for women, respectively. Multivariable logistic regression analyses were used to determine the associations between hyperuricemia and various metabolic abnormalities. In the overall population, hyperuricemia was associated with high blood pressure (odds ratio [OR]: 1.59, and 95% confidence intervals: 1.42–1.77), low high-density lipoprotein (OR: 1.75, 1.56–1.97), high triglycerides (OR: 2.14, 1.90–2.42), high low-density lipoprotein (OR: 1.71, 1.51–1.93), high fasting plasma glucose (OR: 1.29, 1.13–1.48), and central obesity (OR: 2.85, 2.55–3.18) after adjusting for age and serum creatinine concentrations. However, the associations with atherogenic lipid profiles including high triglycerides and high low-density lipoprotein were merely significant in men but not in women. In addition, there was a tendency for a sex difference in the association of hyperuricemia and raised blood pressure ≥130/85 mm Hg, which was greater in women than that in men (OR: 2.92, 1.37–6.25 and 1.54, 1.37–1.72, respectively; P for interaction = .059). Our findings suggest that the association between hyperuricemia and various cardiometabolic abnormalities in young adults may differ by sex, possibly due to a regulation of sex hormones and uneven effects of uric acid at the same levels between sexes on lipid metabolisms and arterial stiffness.